Integrated language skill approach: Model of teaching materials for elementary school teacher education programs in Indonesia - Herlina Usman; Miftahulkhaerah Anwar (Studies in English Language and Education, 2021)
This study is aimed to develop teaching materials, which is an English module for Elementary School Teacher Education Programs in Indonesia based on the integrated language skill approach. A number of 75 respondents from the Elementary School Teacher Education Programs at three universities participated in this research, they are from Universitas Pendidikan Ganesha in Bali, Universitas Mulawarman in Samarinda, and Universitas Negeri Manado in Manado. At the Elementary School Teacher Education Programs, no book with a practical model of integrated language skill is available at these universities. In collecting and analyzing the data, this study combined the research and development (RD) model of Gall et al. (2003). The process comprised four stages to develop this module, they are (1) preliminary studies and needs analysis, (2) product design and development, (3) evaluation, field test, and product revision, (4) and product refinement and dissemination. The data was gained through three instruments from questionnaires, interviews, and formative tests to measure the mastery of English teaching materials for primary school teacher education. The result of this study demonstrated that the module is feasible and effective for English Elementary School Teacher Education Programs at the three universities.